Small-scale demographic structure suggests preemptive behavior in a flocking shorebird - Jutta Leyrer; T Lok; M Brugge; A Dekinga; B Spaans; G van; B Sandercock; T Piersma (2012)
Small-scale demographic structure suggests preemptive behavior in a flocking shorebird